Critical Review on Zeolite Clinoptilolite Safety and Medical Applications in vivo - Kraljević Pavelić, Sandra; Simović Medica, Jasmina; Gumbarević, Darko; Filošević, Ana; Pržulj, Nataša; Pavelić, Krešimir (Frontiers in Pharmacology, 2018)
Unique and outstanding physical and chemical properties of zeolite materials make them extremely useful in a variety of applications including agronomy, ecology, manufacturing, and industrial processes. Recently, a more specific application of one naturally occurring zeolite material, clinoptilolite, has been widely studied in veterinary and human medicine. Due to a number of positive effects on health, including detoxification properties, the usage of clinoptilolite-based products in vivo has increased enormously. However, concerns have been raised in the public about the safety of clinoptilolite materials for in vivo applications. Here, we review the scientific literature on the health effects and safety in medical applications of different clinoptilolite-based materials and propose some comprehensive, scientifically-based hypotheses on possible biological mechanisms underlying the observed effects on the health and body homeostasis. We focus on the safety of the clinoptilolite material and the positive medical effects related to detoxification, immune response, and the general health status.